2021
DOI: 10.1001/jamanetworkopen.2021.38515
|View full text |Cite
|
Sign up to set email alerts
|

Association of Plasma Tau With Mortality and Long-term Neurocognitive Impairment in Survivors of Pediatric Cerebral Malaria and Severe Malarial Anemia

Abstract: Key Points Question Are plasma tau levels associated with long-term neurocognitive impairment in pediatric cerebral malaria or severe malarial anemia? Findings In this cohort study of 467 children in Uganda, including children with cerebral malaria and severe malarial anemia as well as asymptomatic community children, plasma tau levels were higher in children with cerebral malaria or severe malarial anemia compared with asymptomatic community children. Plas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(32 citation statements)
references
References 43 publications
4
28
0
Order By: Relevance
“…The mechanisms of long-term neurological impairment are unknown. Elevated levels of tau in cerebral spinal fluid and increased transcriptions of genes linked to Alzheimer’s disease may be involved [ 289 , 290 ]. In a recent study, examination of the retina revealed that leaks from endothelial cell tight junctions were associated with neurological disability, whereas larger haemorrhagic breaches in the endothelium were associated with brain swelling and death [ 291 ].…”
Section: Molecular Basis Of Severe Disease Phenotypes and Symptomsmentioning
confidence: 99%
“…The mechanisms of long-term neurological impairment are unknown. Elevated levels of tau in cerebral spinal fluid and increased transcriptions of genes linked to Alzheimer’s disease may be involved [ 289 , 290 ]. In a recent study, examination of the retina revealed that leaks from endothelial cell tight junctions were associated with neurological disability, whereas larger haemorrhagic breaches in the endothelium were associated with brain swelling and death [ 291 ].…”
Section: Molecular Basis Of Severe Disease Phenotypes and Symptomsmentioning
confidence: 99%
“…The association of plasma sST2 levels with levels of plasma tau in children with CM [ 43 ] was of particular interest, because it provides a potential pathway through which IL-33/sST2 might lead to long-term neurocognitive impairment. A recent study in this same study cohort demonstrated that plasma tau concentrations were associated with cognitive deficits in children with CM but not SMA [ 44 ], suggesting that long-term neurocognitive impairment may be occurring by a different mechanism in children with CM than SMA. Similarly, in the current study, plasma sST2 levels in children with CM but not in children with SMA were associated with worse cognitive outcomes, despite children in both severe malaria groups demonstrating elevated levels of plasma sST2, suggesting that the ST2 pathway may be more important in brain injury in CM compared to SMA.…”
Section: Discussionmentioning
confidence: 99%
“…In brief, for children <5 years of age, cognitive ability was assessed by the Mullen Scales of Early Learning [36], attention by the Early Childhood Vigilance Test [37], and associative memory by the Color Object Association Test [38]. In children ≥5 years, overall cognitive ability was assessed by the summary mental processing index of the Kaufman Assessment Battery for Children, second edition (KABC-II) [39], attention by the Test of Variables of Attention (D prime measure primary outcome) [40], and working memory by the sequential processing subtest of the K-ABC-II (44). To account for differences in child age, we converted each raw score into a z-score using scores of the community control children.…”
Section: Methodsmentioning
confidence: 99%
“…in 2020: they found that higher CSF tau levels correlated with younger age, increased disease severity (evidenced by low glucose, kidney injury, and prolonged coma death) and an elevated CSF-to-plasma albumin ratio, a marker of BBB breakdown ( Datta et al., 2020 ). In 2021, they demonstrated that plasma tau is also raised in children with CM and is linked to mortality and long-term neurocognitive impairment in children under five ( Datta et al., 2021 ).…”
Section: Biomarkersmentioning
confidence: 99%